Pengaruh Suhu Tinggi terhadap Karakteristik Keramik Cordierite Berbasis Silika Sekam Padi - Sembiring, Simon; Manurung, Posman; Karo-Karo, Pulung (Jurnal Fisika dan Aplikasinya, 2009)
This study was carried out to investigate the effect of high temperature on the functional groups, microstructure and physical characteristics of cordierite ceramics obtained from an aqueous solution of magnesium nitrate hydrate ((Mg(NO3)2.6.12H2O)), aluminium nitrate hydrate (Al(NO3)2.9.15H2O) and silica sols extracted from rice husk. The samples were sintered at temperature of 1000◦C, 1200◦C and 1400◦C. Functional groups and microstructural characteristics of cordierite ceramics were examined by FTIR and SEM, respectivelly. FTIR study shows that the absence of the vibration bands of Na-OH, Si-OH, C-O, Si-O-Si on the samples. However, the formation of cordierite structure was dominated on this high temperature. Microstructure results confirmed the presence of irregular morphology of the solid and compact phases. In addition, the densities, shrinkage andhardness of cordierite increase significantly with increasing temperature, but porosity decreases with increasingtemperature.